PENGARUH DOSIS NITROGEN DAN KALIUM TERHADAP PRODUKSI DAN MUTU TEMBAKAU TEMANGGUNG PADA TUMPANG SISIP KUBIS - TEMBAKAU DI PUJON MALANG - Joedojono Wiroatmodjo; M. Najib (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1995)
The experiment were carried out to determine the effect of N and K on growth, yield and quality of Temanggung tobacco grown intercropped with cabbage at Pujon, Malang. The factorial design with randomized block in five replications were used. Cabbage were planted from February-May, 1992 where as tobacco intercropped in April-September 1993. Three levels of nitrogen from Ammonium Sulphate namely 30 kg N/ha (N1), 60 (N2) and 90 kg N/ha (N3), while Potassium from Potassium Sulphate of 0, 50 and 100 kg K2O/ha were the treatment. Cabbage were fertilization at the rate of 390 kg N/ha and 780 kg P2O5/ha without K fertilization. The first tobacco fertilizations were done at a day after cabbage harvest when tobacco at 16 days old, the half dosages of N and full dosages of K were applied. Other half of N were applied when tobacco at 30 days old. The nitrogen did increase top leaf length, 10 leaf width, fresh yield and N content of Temanggung tobacco of variety of Genjah Kemloko. The potassium did increase quality index and crop index significantly. The N and K interactions is likewise influenced significantly the quality and crop indexes. The maximum leaf length and leaf width were obtained from 90 kg N/ha treatment, whereas highest quality and crop indexes obtained from 30 kg N/ha (N1) and 100 kg K2O/ha (K1) treatments. Highest N content of 3.707% were detected from 90 kg N/ha treatments.